2001
DOI: 10.1523/jneurosci.21-19-07781.2001
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of the Mesoaccumbens Circuit by Serotonin 5-Hydroxytryptamine (5-HT)2Aand 5-HT2CReceptors

Abstract: Serotonin [5-hydroxytryptamine (5-HT)] 5-HT(2A) and 5-HT(2C) receptors (5-HT(2A)Rs and 5-HT(2C)Rs), which innervate the dopamine mesoaccumbens pathway, may play an important role in the behavioral effects of cocaine. To test this hypothesis, the present study measured cocaine-evoked locomotor activity after bilateral microinjection of selective 5-HT(2A)R and 5-HT(2C)R antagonists into the ventral tegmental area (VTA) or the nucleus accumbens (NAc) shell. Locomotor activity was measured after intracranial micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
94
4

Year Published

2002
2002
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 34 publications
14
94
4
Order By: Relevance
“…Intra-VTA injection of the 5-HT 2C R agonist Ro 60-0175 (Fletcher et al, 2004), but not of the 5-HT 2C R antagonist RS 102221 (McMahon et al, 2001), reduced cocaine-induced hyperlocomotion and self-administration. In line with the idea that the VTA may represent a primary site of action for the inhibitory control of the mesoaccumbens DA pathway by 5-HT 2C Rs Grottick et al, 2000;Navailles et al, 2004), it was concluded that VTA 5-HT 2C R stimulation was sufficient to attenuate the locomotor and reinforcing effects of cocaine (Fletcher et al, 2004).…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…Intra-VTA injection of the 5-HT 2C R agonist Ro 60-0175 (Fletcher et al, 2004), but not of the 5-HT 2C R antagonist RS 102221 (McMahon et al, 2001), reduced cocaine-induced hyperlocomotion and self-administration. In line with the idea that the VTA may represent a primary site of action for the inhibitory control of the mesoaccumbens DA pathway by 5-HT 2C Rs Grottick et al, 2000;Navailles et al, 2004), it was concluded that VTA 5-HT 2C R stimulation was sufficient to attenuate the locomotor and reinforcing effects of cocaine (Fletcher et al, 2004).…”
Section: Introductionmentioning
confidence: 89%
“…A stable baseline, defined as three consecutive samples, in which DA contents varied by less than 10%, was generally obtained 135 min after the beginning of the perfusion (stabilization period). Cocaine was diluted in 0.9% NaCl, and administered intraperitoneally at 10 mg/kg in a volume of 2 ml/kg (Filip and Cunningham, 2002;Fletcher et al, 2004;McMahon et al, 2001). The 5-HT 2C R agonist Ro 60-0175 was dissolved in 0.9% NaCl, and administered either into the VTA (1 and 5 mg/0.2 ml, microinjections) or into the NAc (0.1 and 1 mM, reverse dialysis) 15 min before the systemic administration of cocaine.…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%
See 3 more Smart Citations